Hand-lettering for everyone : a creative workbook - Vanko, Cristina (New York, New York : Perigee, 2015)
"In an increasingly digital and impersonal world, hand-lettering is more popular than ever. A way to personalize everything from book covers to T-shirts and restaurant menus, as well as a form of self-expression and cutting-edge design, writing by hand makes the written word immediate and intimate. This beautiful and inviting book serves as an inspiring primer and an interactive workbook. Creative prompts encourage readers to create their own serifs, create lettering from found objects, make a type self-portrait, collage with found type, recreate a favorite book cover with hand-lettering, play with shading and perspective, and more." -- Amazon.com
--History and fundamentals -- Process -- Creative confidence -- Exploration.
Includes bibliographical references.
Keywords: Lettering; Lettering -- Problems, exercises, etc